Self-care of elderly diagnosed with arterial hypertension and/or diabetes mellitus - Marcelle Stephane Nunes de Oliveira; Geovana Brandão Santana Almeida; Denicy de Nazaré Pereira Chagas; Paloma Rodrigues Salazar; Luiza Vieira Ferreira (Universidade Federal de Santa Maria, 2017)
Aim: to understand how the elderly diagnosed with arterial hypertension and/or diabetes mellitus develops their self-care as well as the difficulties they may face. Method: qualitative study with 20 elderly patients diagnosed with arterial hypertension and / or diabetes mellitus. Semi-structured interviews were carried out in a home environment. The data were collected in the months of June and July 2016 and analyzed according to the Content Analysis. Results: three categories were listed through data analysis: Identification of the diagnosis of hypertension and diabetes mellitus; Knowledge of the elderly about arterial hypertension and / or diabetes mellitus; The resources that the elderly uses to take care of arterial hypertension and / or diabetes mellitus. Final considerations: the results revealed that health professionals who assist these elderly people need to rethink effective measures and actions aimed at health education, enabling them to self-care of themselves effectively